Doomsday key - Rollins, James; Fernandez, Peter Jay (New York, N.Y. Harper Audio, 2009)
Commander Gray Pierce and the Sigma Force confront humankind's greatest threat in an adventure that races from the Roman Coliseum to the icy peaks of Norway, from the ruins of medieval abbeys to the lost tombs of Celtic kings. The ultimate nightmare is locked within a talisman buried by a dead saint-- an ancient artifact known as the Doomsday Key-- and a secret that has already claimed the lives of a famed geneticist, a Vatican archaeologist, and a U.S. senator's son.
Unabridged.
Compact discs, digital recording.
Performed by Peter Jay Fernandez.
95809
Keywords: Murder -- Investigation; Cults; Antiquities; Code and cipher stories; Suspense fiction; Adventure fiction; Audiobooks